2004
DOI: 10.1177/00222194040370040301
|View full text |Cite
|
Sign up to set email alerts
|

Season of Birth Is Related to Child Retention Rates, Achievement, and Rate of Diagnosis of Specific LD

Abstract: A sizable literature has demonstrated that the achievement of children in early elementary school is related to their season of birth: Those born in summer typically perform less well than those born in the fall. A small literature indicates that more children diagnosed with specific learning disabilities (SLD) are born in the summer. We have begun to explore the possibility that the same processes may account for both outcomes. In order to better understand these processes, the standardized achievement levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 35 publications
2
73
0
4
Order By: Relevance
“…Although we found that more of the youngest children within cohorts scored above clinical threshold than older children, the present study was not positioned to determine how this translates into higher risk of diagnosis or need of specialist mental health treatment. However, there is evidence that the SDQ is a fairly reliable public health indicator of clinical need [31], and existing research indicates that disproportionately more of the youngest children in a school cohort are likely to be receiving psychology services and intervention [7] and special educational needs assessment [12,32].…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Although we found that more of the youngest children within cohorts scored above clinical threshold than older children, the present study was not positioned to determine how this translates into higher risk of diagnosis or need of specialist mental health treatment. However, there is evidence that the SDQ is a fairly reliable public health indicator of clinical need [31], and existing research indicates that disproportionately more of the youngest children in a school cohort are likely to be receiving psychology services and intervention [7] and special educational needs assessment [12,32].…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…However, it is difficult to partition out the relative contributions of a btrueQ season of birth effect on neurocognitive development from the fact that summer-born infants in northern hemisphere countries tend to be educationally disadvantaged (due to the interaction between age and school intake policies) (Goodman et al, 2003). A recent US study of children in the fifth grade (n = 7395), confirmed that summer-born children did significantly worse on a range of standardized educational tests, and that these seasonal differences persisted when the children outside the appropriate age band (i.e., dretainedT or dadvancedT students) were excluded (Martin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The research that has examined season of birth and later cognitive development have produced mixed results (Gordon and Novak, 1950;Berglund, 1967;Farley, 1968;Williams et al, 1970;Kanekar and Mukerjee, 1972;Mascie-Taylor, 1980). With respect to school performance, there is a sizeable body of research showing that summer-born children tend to have poorer educational outcomes (see review by (Martin et al, 2004)). However, it is difficult to partition out the relative contributions of a btrueQ season of birth effect on neurocognitive development from the fact that summer-born infants in northern hemisphere countries tend to be educationally disadvantaged (due to the interaction between age and school intake policies) (Goodman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This effect is observed both with regard to various subject skills (Bell and Daniels, 1990;Hutchison and Sharp, 1999;Konarzewski, 2013;Martin, Foels, Clanton and Moon, 2004;Smith, 2009), as well as broadly understood teaching results, such as motivation, involvement in learning or attitude towards school and teaching (Martin, 2009). Some researchers focus on the situation of the youngest students in a class among children born in the same year and prove that these children more often experience school failures, such as not being promoted to the next class or being assessed as having special education needs (Langer, Kalk and Searls, 1984;Martin et al, 2004;May and Kundert, 1995;Verachtert, De Fraine, Onghena and Ghesquière, 2010). These results support the hypothesis that students' age is significant for school achievement.…”
Section: Age Effect On School Achievementmentioning
confidence: 91%
“…The reader who is interested in such analyses can find interesting hypotheses in the studies of other authors (Konarzewski, 2013;Martin et al, 2004;Sykes, Bell and Vidal Rodeiro, 2009;Verachtert et al, 2010).…”
Section: Dependent Variable: Relative Increases In School Achievementmentioning
confidence: 97%